Proteasome Inhibition Suppresses KIT-Independent Gastrointestinal Stromal Tumors Via Targeting Hippo/YAP/Cyclin D1 Signaling - Chen, Ting; Ni, Nan; Yuan, Li; Xu, Liangliang; Bahri, Nacef; Sun, Boshu; Wu, Yuehong; Ou, Wen-Bin (Frontiers in Pharmacology, 2021)
Purpose: Gastrointestinal stromal tumors (GISTs) are the most common malignant tumor of mesenchymal origin of the digestive tract. A yet more challenging resistance mechanism involves transition from oncogenic KIT to a new imatinib-insensitive oncogenic driver, heralded by loss of KIT expression. Our recent studies have shown that inhibition of cyclin D1 and Hippo signaling, which are overexpressed in KIT-independent GIST, is accompanied by anti-proliferative and apoptosis-promoting effects. PRKCQ, JUN, and the Hippo/YAP pathway coordinately regulate GIST cyclin D1 expression. Thus, targeting of these pathways could be effective therapeutically for these now untreatable tumors. Methods: Targeting cyclin D1 expression of small molecular drugs was screened by a cell monolayer growth and western blotting. The biologic mechanisms of bortezomib to KIT-independent GISTs were assessed by immunoblotting, qRT-PCR, cell viability, colony growth, cell cycle analysis, apoptosis, migration and invasiveness. Results: In the initial small molecular inhibitor screening in KIT-independent GIST62, we found that bortezomib-mediated inhibition of the ubiquitin-proteasome machinery showed anti-proliferative effects of KIT-independent GIST cells via downregulation of cyclin D1 and induction of p53 and p21. Treatment with proteasome inhibitor, bortezomib, led to downregulation of cyclin D1 and YAP/TAZ and an increase in the cleaved PARP expression in three KIT-independent GIST cell lines (GIST48B, GIST54, and GIST226). Additionally, it induced p53 and p21 expression in GIST48B and GIST54, increased apoptosis, and led to cell cycle G1/G2-phase arrest, decreased cell viability, colony formation, as well as migration and invasiveness in all GIST cell lines. Conclusion: Although our findings are early proof-of-principle, there are signs of a potential effective treatment for KIT-independent GISTs. The data highlight that targeting of cyclin D1 and Hippo/YAP by bortezomib warrants evaluation as a novel therapeutic strategy in KIT-independent GISTs.